2005
DOI: 10.1111/j.1365-2222.2005.02388.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with depigmented glutaraldehyde‐polymerized extracts: changes in quality of life

Abstract: In [1], on page 574, the text of the second paragraph has a mistake (in bold): ''Two vials were prepared to be used as a therapeutic vaccine. Vial no. 2 contained 270 mg of D. glomerata and 280 mg of O. europaea, which were the result of depigmenting and polymerizing 100 HEP L , corresponding to 750 mg of freeze-dried extract of D. glomerata (60 mg/mL Dac g 2, 20 mg/mL Dac g 115) and 3550 mg of freeze-dried extract of O. europaea (131 mg/mL Ole e 1). Vial no. 1 was a 10-fold dilution of vial no. 2.''The correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 1 publication
4
29
0
1
Order By: Relevance
“…The size of response to treatment seen in our study is comparable with that noted in previous studies of immunotherapy with unmodified birch pollen extract [9, 10, 32, 33]. This is the first study to report improvement in rhinitis QOL scores following immunotherapy with a depigmented polymerized birch pollen extract, although this has been reported for patients sensitive to grass pollens and HDM [20, 22]. Of note, some of these studies did show significant reductions in symptom scores, which was not observed in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The size of response to treatment seen in our study is comparable with that noted in previous studies of immunotherapy with unmodified birch pollen extract [9, 10, 32, 33]. This is the first study to report improvement in rhinitis QOL scores following immunotherapy with a depigmented polymerized birch pollen extract, although this has been reported for patients sensitive to grass pollens and HDM [20, 22]. Of note, some of these studies did show significant reductions in symptom scores, which was not observed in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Although we did not compare the results in the different treatment arms with a pure placebo group, we were able to answer our original research question, which was to demonstrate the superiority of the combined treatment over SIT alone. Anyway, the superiority of these both treatment options over placebo has already been shown in previous reports [17–20, 31–33]. There are now several open‐label studies which have shown that SIT also lowers the onset of new sensitization and the progression from allergic rhinoconjunctivitis to bronchial asthma [34, 35].…”
Section: Discussionmentioning
confidence: 89%
“…Clinical efficacy (reduction of symptoms and/or need for medications) has been confirmed with grass (1102,1104,(1650)(1651)(1652)(1653)(1654)(1655), birch (1650,1651,(1656)(1657)(1658)(1659), ragweed (1660), Russian thistle (1661), Parietaria pollen (1662,1663), mites (1664)(1665)(1666)(1667)(1668)(1669) and cat (1670). It should be noted that three of the studies (1104,1660,1670) clearly demonstrated that the clinical effect is dose dependent.…”
Section: Aria: 2008 Updatementioning
confidence: 98%